2018
DOI: 10.1115/1.4038361
|View full text |Cite
|
Sign up to set email alerts
|

Re-Ingestion of Upstream Egress in a 1.5-Stage Gas Turbine Rig

Abstract: In gas turbines, rim seals are fitted at the periphery of stator and rotor discs to minimize the purge flow required to seal the wheel-space between the discs. Ingestion (or ingress) of hot mainstream gases through rim seals is a threat to the operating life and integrity of highly stressed components, particularly in the first-stage turbine. Egress of sealing flow from the first-stage can be re-ingested in downstream stages. This paper presents experimental results using a 1.5-stage test facility designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Scobie et al [18] studied ingress and egress in a 1.5-stage turbine test rig and quantified the egress flow from the upstream wheelspace cavity that is ingested into the downstream wheelspace cavity. In their study, the authors used effectiveness measurements and radial traverses upstream and downstream of the turbine blade to study the effects of cooling flow being "carried over" into the following wheelspace cavity by re-ingestion.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Scobie et al [18] studied ingress and egress in a 1.5-stage turbine test rig and quantified the egress flow from the upstream wheelspace cavity that is ingested into the downstream wheelspace cavity. In their study, the authors used effectiveness measurements and radial traverses upstream and downstream of the turbine blade to study the effects of cooling flow being "carried over" into the following wheelspace cavity by re-ingestion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One full vane pitch of data was collected at 0.1 vane pitch increments, as well as a total of 22 points in the radial direction were collected. A higher number of points were collected near the inner diameter wall to better resolve the gradient of CO 2 egressed from the wheelspace cavity that migrates along the inner turbine wall as described by Scobie et al [18]. Each radial location data point in the two figures is an average of the ten pitch increment points that covered the full vane pitch in the circumferential direction.…”
Section: Flow Migration Into the Main Gas Path Flowmentioning
confidence: 99%
“…They measured an asymmetric egress distribution in the annulus at the edge of the seal clearance, driven by the annulus pressure profile. Scobie et al [8] quantified the re-ingestion of the upstream hub cavity purge into the downstream one, using seed gas concentration measurements. They concluded that the upstream injection partially mixes with the annulus air stream close to the downstream seal, reducing the adverse effects of ingress.…”
mentioning
confidence: 99%